2010
DOI: 10.1007/s11665-010-9724-z
|View full text |Cite
|
Sign up to set email alerts
|

Fluid/Structure Interaction Computational Investigation of Blast-Wave Mitigation Efficacy of the Advanced Combat Helmet

Abstract: To combat the problem of traumatic brain injury (TBI), a signature injury of the current military conflicts, there is an urgent need to design head protection systems with superior blast/ballistic impact mitigation capabilities. Toward that end, the blast impact mitigation performance of an advanced combat helmet (ACH) head protection system equipped with polyurea suspension pads and subjected to two different blast peak pressure loadings has been investigated computationally. A fairly detailed (Lagrangian) fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 18 publications
2
74
0
Order By: Relevance
“…In other words, a vast body of experimental studies pertaining to the blast/ballistic-protection performance of various polyurea bearing protective structures was not the subject of the present investigation. An overview of the latter investigations can be found in our prior work (Ref [16][17][18][19][20][21].…”
Section: Overview Of the Prior Experimental Investigationsmentioning
confidence: 99%
“…In other words, a vast body of experimental studies pertaining to the blast/ballistic-protection performance of various polyurea bearing protective structures was not the subject of the present investigation. An overview of the latter investigations can be found in our prior work (Ref [16][17][18][19][20][21].…”
Section: Overview Of the Prior Experimental Investigationsmentioning
confidence: 99%
“…For both 5.2 atm and 18.6 atm blast intensities, no shear-induced mTBI was observed, while there was a possibility of contusion type TBI. For a head protected by a helmet, the findings obtained by Grujicic et al [62] were contradictory to those reported in Moore et al [93] and Nyein et al [104]. For the helmeted head, the load transfer path to the skull was found to be different.…”
Section: Ballistic Helmet and Traumatic Brain Injurymentioning
confidence: 80%
“…In the absence of information about the currently used suspension pad material in the ACH, Ethylene-Vinyl-Acetate (EVA) was chosen as a second material (other than polyurea). The material models and the pressure intensities were taken to be the same as those used in their earlier study [62]. High peak axial stresses and peak particle velocities were chosen as parameters for comparison.…”
Section: Ballistic Helmet and Traumatic Brain Injurymentioning
confidence: 99%
“…The precise mechanisms by which bTBI occurs are still unknown. Grujicic et al [10] propose that rotational motion and acceleration/deceleration are not applicable in blast-induced trauma scenarios. Conversely, an investigation by Dagro et al [11] supports the notion that rotational loading is relevant to blast events.…”
Section: Introductionmentioning
confidence: 99%
“…Axonal damage, cerebral contusion and subdural haemorrhaging are the three most common forms of mild TBI (mTBI), or concussion as it is known in common language [10]. Of these three forms of mTBI, DAI is the most difficult to detect by conventional means such as computed tomography (CT) scan or magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%